2016
DOI: 10.1002/ajpa.22981
|View full text |Cite
|
Sign up to set email alerts
|

Neandertals' large lower thorax may represent adaptation to high protein diet

Abstract: Humans are limited in their capacity to convert protein into energy. We present a hypothesis that a "bell" shaped thorax and a wide pelvis evolved in Neandertals, at least in part, as an adaptation to a high protein diet. A high protein diet created a need to house an enlarged liver and urinary system in a wider lower trunk. To test the hypothesis, we applied a model developed to identify points of nutritional stress. A ratio of obligatory dietary fat to total animal fat and protein sourced calories is calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 130 publications
1
21
0
Order By: Relevance
“…One such adaptation is the move towards an increasingly meat‐rich diet in later species of Homo . It has been suggested that the barrel‐shaped thorax of Neanderthals evolved to accommodate the necessary increase in liver size and urinary system size for a species that may have been reliant on a diet of up to 85% animal fat during glacial winters (Ben‐Dor et al ., ). This complements the theory discussed earlier that Neanderthal morphologies were adapted to encourage heat production, as studies have indicated that a high protein diet considerably increases heat production from metabolism (Snodgrass and Leonard, ).…”
Section: Technological Buffering and Optimizationsupporting
confidence: 74%
“…One such adaptation is the move towards an increasingly meat‐rich diet in later species of Homo . It has been suggested that the barrel‐shaped thorax of Neanderthals evolved to accommodate the necessary increase in liver size and urinary system size for a species that may have been reliant on a diet of up to 85% animal fat during glacial winters (Ben‐Dor et al ., ). This complements the theory discussed earlier that Neanderthal morphologies were adapted to encourage heat production, as studies have indicated that a high protein diet considerably increases heat production from metabolism (Snodgrass and Leonard, ).…”
Section: Technological Buffering and Optimizationsupporting
confidence: 74%
“…That large DEE must be caused for their large brains (Fig. 3, Table 3) and large lean body mass (Table 3), but alternative explanations such as the possibility that Neanderthals had large guts (liver and urinary systems) necessary for processing large amounts of meat, could also be linked with high DEE 52 .
Fig. 3 a Thorax and lungs' shape in the frontal view in modern humans and Neanderthals and their associated brains in the lateral view.
…”
Section: Discussionmentioning
confidence: 99%
“…As at least some of the items mentioned in the data provided above were also manufactured and used by prehistoric groups (e.g., spears and projectiles), and given the technological and cognitive abilities attributed to Lower and Middle Paleolithic populations, and as the profits which could have been yielded from an elephant carcass were abundant and significant, we strongly believe that at least some of the above-presented strategies were also applied by prehistoric people. Furthermore, although some claim that the hunting of large-sized prey was too costly in terms of cost-benefit, compared to that of small game, making such large prey "inefficient choices" [8], it is our contention that elephants played a main role in the Paleolithic diet, providing an abundant supply of meat and fat, in a way unparalleled by any other prey [16], and, hence, were hunted and procured when available and needed.…”
Section: Discussionmentioning
confidence: 91%